ANALISIS PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL DAN OPERATING LEVERAGE TERHADAP PROFITABILITAS SAHAM-SAHAM LQ 45 DI BURSA EFEK INDONESIA - Yosi Stefhani (Jurnal Manajemen, 2019)
The purpose of this research is to look at the effect of company size, capital structure and operating leverage on the profitability of stocks including LQ 45 shares on the Indonesia Stock Exchange. The sample in this research is LQ 45 shares in the period 2018. The indicators used from the variables studied are (1) the size of the company using the indicator of total assets (2) capital structure using the Debt to Equity Ratio (DER) indicator ( 3) operating leverage using the Degree Operating Leverage (DOL) indicator and (4) profitability using the Earning Per Share (EPS) indicator. The data analysis method used is multiple regression analysis. The results of the research show that partially only company size affects profitability while the capital structure and operating leverage partially do not affect profitability. But simultaneously the size of the company, capital structure and operating leverage have influence profitability.